2021
DOI: 10.1002/anie.202104859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of External Surface Diffusion Barriers on Platinum/Beta‐Catalyzed Isomerization of n‐Pentane

Abstract: We have developed a generalizable strategy to quantify the effect of surface barriers on zeolite catalysis. Isomerization of n‐pentane, catalyzed by Pt/Beta, is taken as a model reaction system. Firstly, the surface modification by chemical liquid deposition of SiO2 was carried out to control the surface barriers on zeolite Beta crystals. The deposition of SiO2 leads to a very slight change in the physical properties of Beta crystals, but an obvious reduction in Brønsted acid sites. Diffusion measurements by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 44 publications
0
27
0
1
Order By: Relevance
“…Alkyl PAs were generally found to bind to the external surface of the zeolite, slowing transport of various gases into the zeolite crystals. By manipulating the chemistry of the PA tail groups to preferentially attract or repel particular gases, it may be possible to selectively retard transport to the interior of the zeolite, providing a new basis for selectivity control . More complex scenarios are also possible.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkyl PAs were generally found to bind to the external surface of the zeolite, slowing transport of various gases into the zeolite crystals. By manipulating the chemistry of the PA tail groups to preferentially attract or repel particular gases, it may be possible to selectively retard transport to the interior of the zeolite, providing a new basis for selectivity control . More complex scenarios are also possible.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…By manipulating the chemistry of the PA tail groups to preferentially attract or repel particular gases, it may be possible to selectively retard transport to the interior of the zeolite, providing a new basis for selectivity control. 51 More complex scenarios are also possible. For example, the shortchain methyl PA was found to penetrate the subsurface region of the 5A zeolite crystals, creating a structure that more dramatically influenced gas diffusion into the pores.…”
Section: ■ Perspectives and Conclusionmentioning
confidence: 99%
“…12C, right). 35 They found that the surface barriers were reduced by surface deposition of a silica layer. As a result, the apparent catalytic activity was remarkably improved.…”
Section: Spatial Diffusion Paths In the Micro-zones Of Model Zeolite ...mentioning
confidence: 99%
“…16 The surface barrier, which may originate from surface defects, has been widely discussed and considered as another important diffusion mechanism. [17][18][19] Pure nanosheet zeolite with discontinuity along the b-axis direction produces a large amount of extraframework Al and external Si-OH, which may increase the surface barrier. It has been found that compared with bulk ZSM-5, the spent nanosheet zeolite deposits more coke after 100 h of n-heptane cracking.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The reduction of the surface barrier after silica deposition makes the Pt/Beta zeolite exhibit 131% increase in catalytic activity. 17 Although the two-dimensional nanosheets achieve an ultra-short diffusion pathlength, the external surface barrier may be another consideration for adjusting the catalytic performance of the nanosheet zeolite.…”
Section: Introductionmentioning
confidence: 99%